Cationic nanoparticles self-assembled from amphiphilic chitosan derivatives containing poly(amidoamine) dendrons and deoxycholic acid as a vector for co-delivery of doxorubicin and gene. (15th April 2021) - Chen, Shanshan; Deng, Junjie; Zhang, Li-Ming
Highlights: Hydrophobic modified and poly(amidoamine) dendronized chitosan amphiphilic derivatives were synthesized and characterized. The cationic NPs self-assembled from the chitosan derivatives were able to co-deliver doxorubicin and pDNA. The as-prepared NPs had low cytoxicity and could achieve a transfection efficiency up to 74 % in the 293 T cells. Low dosage of co-delivered doxorubicin could enhance the gene transfection, showing a synergistic effect. Abstract: Combination treatment through the co-delivery of drugs and genes by nanoformulations may achieve a synergistic effect. In our previous study, poly(amidoamine) dendronized chitosan derivative (PAMAM-Cs) showed good gene transfection efficiency and low cytotoxicity. Here, we incorporated hydrophobic deoxycholic acid (DCA) onto the chitosan backbone of PAMAM-Cs to obtain an amphiphilic derivative—PAMAM-Cs-DCA, which could self-assemble into cationic nanoparticles (NPs). The resulting NPs with diameters of 140–220 nm can encapsulate the hydrophobic anticancer drug doxorubicin (DOX) in the core while bind pDNA via the positively charged PAMAM shell. PAMAM-Cs-DCA NPs could completely complex with pDNA at a ratio of nitrogen to phosphorous (N/P) low as 1 and the complexes achieved a transfection efficiency up to 74 % at N/P 20. Moreover, low-dose co-delivered DOX could enhance the transgene expression, showing a synergistic effect. These results suggest that PAMAM-Cs-DCA NPs hold great promise to co-deliver chemotherapeutics and nucleic acid drugs.